Statistical aspects of water quality monitoring : proceedings of the workshop held at the Canada Centre for Inland Waters, October 7-10, 1985 - El-Shaarawi, A. H.; Kwiatkowski, R. E., 1949-; ScienceDirect eBooks (Amsterdam ; New York : Elsevier ; New York, N.Y., U.S.A. : Distributors for the United States and Canada, Elsevier Science Pub. Co., 1986)
This volume contains selected papers from the ``Workshop on the Statistical Aspects of Water Quality Monitoring'', held on October 7-10 1985, at the National Water Research Institute in Burlington, Ontario, Canada. The prime objective of the Workshop was to generate interaction between the statistical community and scientists working in the area of Water Quality Monitoring. To this end, topics covered in this Workshop fall into two categories: (1) Methods Development, and (2) the Imaginative Application of Existing Methodologies. Subjects covered include: Time Series, Estimation of Loading, Clustering, Model Development, Censoring Data Analysis, Quality Control and Data Acquisition. In the area of environmental sciences, statistical applications are still in their infancy, with few attempts to systematically develop techniques dealing with environmental issues. The publication of this book is one step towards identifying appropriate statistical techniques and diagnosing problems in Water Quality Monitoring which require new statistical methodologies. The papers presented in this volume represent international expertise, consolidating detailed information on both conventional and new methods.
Front Cover; Statlstlcal Aspects of Water Quality Monitoring; Copyright Page; Preface; Contents; Chapter 1. Spatial Heterogeneity of Water Quality Parameters; Chapter 2. Uncertainty in Water Quality Data; Chapter 3. The Use of Multivariate Methods in the Interpretation of Water Quality Monitoring Data of a Large Northern Reservoir; Chapter 4. Modeling River Acidity -- A Transfer Function Approach; Chapter 5. Sulphate, Water Colour and Dissolved Organic Carbon Relationships in Organic Waters of Atlantic Canada.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Water quality -- Measurement -- Congresses; Water quality -- Statistical methods -- Congresses; TECHNOLOGY & ENGINEERING -- Environmental -- Water Supply; Water quality -- Measurement; Water quality -- Statistical methods; Water -- Quality control -- Statistical methods; Electronic books